Development of a Guided Inquiry-Based E-Module to Optimize Student's Conceptual Understanding of Buffer Solution Material - Istijabah Mufsiroh; Kasmui Kasmui (Universitas Negeri Semarang, 2026)
This study aims to develop a guided inquiry-based e-module to optimize student’s conceptual understanding of buffer solution material. The research employed the 4D development model, limited to the development stage (3D). The e-module was designed using the Google Sites platform and equipped with interactive features such as instructional videos, virtual laboratories, and Wordwall educational games. The trial subjects included students from SMA Muhammadiyah 1 Temanggung (small scale) and SMA Negeri 1 Temanggung (large scale). Expert validation indicated that the e-module was highly feasible in terms of content and media. Validation by subject matter experts yielded a score of 88.37%, categorized as “very valid”, while media experts gave a score of 95.16%, also categorized as “very high”. The effectiveness of the e-module was evidenced by a significant increase in student’s conceptual understanding scores, with an n-gain of 0.8260, as well as positive student responses to the learning media. Therefore, the develop e-module is considered feasible, effective, and enganging for teaching buffer solution material in chemistry learning.